Denosumab: Renal Safety Evaluation. Issue 2 (May 2017) - Malberti, Fabio; Foramitti, Marina
Denosumab, a fully human monoclonal antibody against the receptor activator of nuclear factor kappa B ligand (RANKL), has been approved for the prevention of skeletal-related events in metastatic solid tumor patients with bone metastases. As opposed to the bisphosphonates, denosumab is not excreted by the kidney, and renal function does not have a significant effect on denosumab pharmacokinetics or pharmacodynamics. Thus, dose adjustment is not required in patients with renal insufficiency. In contrast to the bisphosphonates, denosumab has not been documented to have nephrotoxic effects. However, it does share some toxicities with bisphosphonates, including hypocalcemia and osteonecrosis of the jaw. In this review, the warnings and recommendations for the use of denosumab in patients with renal insufficiency are discussed.